ANALISIS NILAI PENDIDIKAN KARAKTER DALAM SERAT WULANGREH KARYA SRI SUSUHUNAN PAKUBUWONO IV - Iskandar, Maulana; Mukminin, Amir (PERMAI: Jurnal Pendidikan dan Literasi Madrasah Ibtida'iyah, 2023)
Sri Susuhunan Pakubuwono IV wrote advice full of meaning and character values in the fiber of Wulangreh. The content research supported by descriptive analysis was taken by the researcher to analyze the verses of the tembang which implied several character values from the 18 character values initiated by the Ministry of National Education. The study results show several valuescontained in Wulangreh fiber: a religious, peace-loving, hard work, love for the homeland, and fondness for reading.Keywords : Tembang, Characters Building, Wulangreh